The molten-globule residual structure is critical for reflavination of glucose oxidase - Garajová, Katarína; Zimmermann, Martina; Petrenčáková, Martina; Dzurová, Lenka; Nemergut, Michal; Škultéty, Ľudovít; Žoldák, Gabriel; Sedlák, Erik (Biophysical chemistry, 2017)
Glucose oxidase (GOX) is a homodimeric glycoprotein with tightly bound one molecule of FAD cofactor per monomer of the protein. GOX has numerous applications, but the preparation of biotechnologically interesting GOX sensors requires a removal of the native FAD cofactor. This process often leads to unwanted irreversible deflavination and, as a consequence, to the low enzyme recovery. Molecular mechanisms of reversible reflavination are poorly understood; our current knowledge is based only on empiric rules, which is clearly insufficient for further development. To develop conceptual understanding of flavin-binding competent states, we studied the effect of deflavination protocols on conformational properties of GOX. After deflavination, the apoform assembles into soluble oligomers with nearly native-like holoform secondary structure but largely destabilized tertiary structure presumambly due to the packing density defects around the vacant flavin binding site. The reflavination is cooperative but not fully efficient; after the binding the flavin cofactor, the protein directly disassembles into native homodimers while the fraction of oligomers remains irreversibly inactivated. Importantly, the effect of Hofmeister salts on the conformational properties of GOX and reflavination efficiency indicates that the native-like residual tertiary structure in the molten-globule states favorably supports the reflavination and minimizes the inactivated oligomers. We interpret our results by combining the ligand-induced changes in quaternary structure with salt-sensitive, non-equilibrated conformational selection model. In summary, our work provides the very first steps toward molecular understanding the complexity of the GOX reflavination mechanism.
Keywords: Hofmeister anions; glukosaoxidasa; Thermal stability; Calorimetry, Differential Scanning; Protein Structure, Tertiary; teplota; stabilita proteinů; Glucose Oxidase; Homodimeric interface; flavinadenindinukleotid; terciární struktura proteinů; Protein Stability; spektrofotometrie ultrafialová; diferenciální skenovací kalorimetrie; Flavin-Adenine Dinucleotide; Protein Multimerization; biokatalýza; Temperature; Protein Structure, Secondary; Circular Dichroism; Aspergillus niger; Protein Isoforms; Spectrophotometry, Ultraviolet; sekundární struktura proteinů; multimerizace proteinu; protein - isoformy; Deflavination; Biocatalysis; cirkulární dichroismus